Phonological Rhetoric of Submission in the Qur’an: A Stylistic Analysis of the Fifteen Sajdah Verses - Hanifa, Zahra Aulia; Dewi, Dita Puspita; Sopian, Asep (Jurnal Adabiyah, 2026)
This study examines how the sound system in the verses of sajdah functions not only as beauty, but as a rhetorical device that reinforces the meaning of submission (sujūd). Departing from the Leech–Short stylistic framework and the concept of foregrounding, this study formulates the idea of "the phonological rhetoric of submission" to formalize the role of assonance, alliteration, rhyme, and rhythm as strategies that evoke emotions and encourage worship practice. The study employs manual IPA-based phonetic transcription and foregrounding analysis across fifteen sajdah verses. This study maps the sound pattern and its rhetorical function, then validates the results through triangulation of meanings to be linguistically and theologically aligned. The findings show a consistent and meaningful sound configuration: back/long vowels (/u/, /ā/) present a soft resonance that emphasizes solemn nuances; a series of emphatic consonants (/r/,/q/,/ṭ/) denote divine imperatives; The parallelism of rhyme and rhythm builds musical coherence and spiritual upliftment. This framework advances Qur’anic stylistics by operationalizing phonology as a rhetorical mechanism rather than an aesthetic byproduct. Theoretically, this study offers a framework of "the phonological rhetoric of submission" in the stylistics of the Qur'an; methodologically, integrating foregrounding analysis with interpretation validation; practically, it opens the direction of the Qur'an's pedagogy based on prosody that associates sound markers with the understanding of sajdah verses. خلاصة تبحث هذه الدراسة في كيفية عمل النظام الصوتي في آيات السجدة لا بوصفه جمالًا فحسب، بل بوصفه أيضًا أداةً بلاغية تُعزِّز معنى الخضوع (السجود). وانطلاقًا من إطار ليتش–شورت الأسلوبي ومفهوم البروز (foregrounding)، تُبلور هذه الدراسة فكرة «البلاغة الفونولوجية للخضوع» لتقنين دور التوافق الصوتي (assonance) والجناس الاستهلالي (alliteration) والقافية والإيقاع بوصفها استراتيجيات تُثير الانفعالات وتدفع إلى ممارسة العبادة. وتعتمد الدراسة على التفريغ الصوتي اليدوي القائم على الأبجدية الصوتية الدولية (IPA) وتحليل البروز عبر خمس عشرة آيةً من آيات السجدة. وتقوم هذه الدراسة برسم خريطة لأنماط الصوت ووظائفها البلاغية، ثم تُثبّت النتائج عبر تثليث المعنى لضمان اتساقها لغويًا ولاهوتيًا. وتُظهر النتائج تهيئةً صوتيةً متّسقة وذات دلالة: فالحركات الخلفية/الطويلة (/u/، /ā/) تُحدث رنينًا لطيفًا يُبرز دلالات الخشوع والوقار؛ وسلسلة من الصوامت المفخّمة (/r/، /q/، /ṭ/) تُشير إلى الأوامر الإلهية؛ كما يبني التوازي في القافية والإيقاع تماسكًا موسيقيًا وسموًّا روحيًا. ويُسهم هذا الإطار في تطوير أسلوبيات القرآن الكريم عبر تشغيل الفونولوجيا بوصفها آليةً بلاغية لا مجرد أثرٍ جمالي. وعلى المستوى النظري، يقدّم البحث إطار «البلاغة الفونولوجية للخضوع» ضمن أسلوبيات القرآن؛ وعلى المستوى المنهجي، يدمج تحليل البروز مع تثبيت التأويل؛ وعلى المستوى التطبيقي، يفتح مسارًا لتربيةٍ قرآنية قائمة على العَروض/الإيقاع تربط العلامات الصوتية بفهم آيات السجدة. Abstrak Penelitian ini mengkaji bagaimana sistem bunyi dalam ayat-ayat sajdah berfungsi bukan hanya sebagai keindahan, tetapi juga sebagai perangkat retoris yang memperkuat makna kepasrahan (sujūd). Berangkat dari kerangka stilistika Leech–Short dan konsep foregrounding, penelitian ini merumuskan gagasan “retorika fonologis kepasrahan” untuk memformalkan peran asonansi, aliterasi, rima, dan ritme sebagai strategi yang membangkitkan emosi dan mendorong praktik ibadah. Penelitian ini menggunakan transkripsi fonetik manual berbasis IPA dan analisis foregrounding pada lima belas ayat sajdah. Penelitian ini memetakan pola bunyi beserta fungsi retorisnya, lalu memvalidasi hasilnya melalui triangulasi makna agar selaras secara linguistik dan teologis. Temuan menunjukkan konfigurasi bunyi yang konsisten dan bermakna: vokal belakang/panjang (/u/, /ā/) menghadirkan resonansi lembut yang menegaskan nuansa kekhusyukan; rangkaian konsonan tafkhīm/tegas (/r/, /q/, /ṭ/) menandai imperatif ilahi; paralelisme rima dan ritme membangun koherensi musikal dan pengangkatan spiritual. Kerangka ini memajukan stilistika Al-Qur’an dengan mengoperasionalisasikan fonologi sebagai mekanisme retoris, bukan sekadar produk sampingan estetika. Secara teoretis, penelitian ini menawarkan kerangka “retorika fonologis kepasrahan” dalam stilistika Al-Qur’an; secara metodologis, mengintegrasikan analisis foregrounding dengan validasi interpretasi; secara praktis, membuka arah pedagogi Al-Qur’an berbasis prosodi yang mengaitkan penanda bunyi dengan pemahaman ayat-ayat sajdah.